The impact of innovation on CO2 emissions: the threshold effect of financial development - Yu, Danni; Soh, Wei Ni; Amin Noordin, Bany Ariffin; Yahya, Mohamed Hisham; Latif, Badar (Frontiers Media, 2022)
We show that innovative activities exacerbate environmental degradation based on data covering 52 countries between 1990 and 2014. Yet, innovative activities carried out in countries with greater financial development pose less environmental harm. Additionally, we show the equity market is more effective concerning dampening effect of innovation on carbon emissions. With a dynamic panel threshold method, we find that innovation is significantly associated with improvements in environmental quality when the private sector credit and market capitalization of listed domestic companies exceed threshold levels of about 65 and 16% as a share of GDP respectively. We also look into the relationship between financial structure and the innovation-pollution nexus. We show that innovation promotes environmental quality in countries that have a relatively more equity-based financial system. Our empirical evidence calls for policymakers to identify the optimal level of finance to mitigate pollution resulting from innovative activities and realign the financial structure in accordance with the innovation-pollution nexus.